Reduction of Fish Production in Hakaluki Haor Caused by Climatic and Anthropogenic Factors - Aziz, Md Saifullah Bin; Alam, Md Mehedi; Haque, Mohammad Mahfujul; Mondol, Md Mostafizur Rahman (Journal of Bio-Science, 2023)
A study was conducted to examine the various factors influencing the decline in fish production in the Hakaluki Haor wetland ecosystem in northeast Bangladesh, aiming to investigate the impacts of both climatic and anthropogenic factors on fish production in the area. Nowadays, this wetland is increasingly impacted by climate change, which poses significant challenges to fish production and sustainability. The primary data were collected through a face-to-face questionnaire survey (n = 150) with fishers, focus group discussion (n =15), and key informant interviews (n = 10). The majority of the fishers were middle-aged group (31-50 year), whereas 41% had primary level (schooling year 5) of education and 48% were highly experienced fishermen (≤16 years). Stakeholder perceptions of human activities, including overfishing (52%), discard of non-target species (23%), use of destructive fishing gear (67%), beel drying (47%), habitat destruction (48%), water pollution (23%), migration route changes (30%) and agricultural intensification (45%), have been identified to reduce fish production. Additionally, the study revealed that climate change impacts the ecosystem, including temperature fluctuation (57%), erratic rainfall (49%), flood and flash flood (37%), drought (17%), and siltation in beel (37%). Stakeholders perceived these impacts to have significant negative effects on aquatic biodiversity, particularly in terms of habitat destruction and water quality degradation. This study proposes potential solutions to mitigate the impacts of climate changes and man-made factors associated with fish production reduction in the region, such as improved water management practices, diversification of fish species, and the use of climate-resilient fisheries management. Community engagement and government support are highlighted as crucial factors to address the impacts of climate change on fish production in Hakaluki Haor. The findings of this study have important implications for the development of effective management strategies for ensuring sustainable livelihoods for fishers. J. Bio-Sci. 30(2): 23-37, 2022